Clinical outcomes stratified by baseline functional class after initial combination therapy for pulmonary arterial hypertension - White, R. James; Grünig, Ekkehard (Respiratory research, 2019)
Background: Initial combination therapy with ambrisentan and tadalafil reduced the risk of clinical failure events for treatment-naïve participants with pulmonary arterial hypertension (PAH) as compared to monotherapy. Previous studies in PAH have demonstrated greater treatment benefits in more symptomatic participants. Methods: AMBITION was an event-driven, double-blind study in which participants were randomized 2:1:1 to once-daily initial combination therapy with ambrisentan 10 mg plus tadalafil 40 mg, ambrisentan 10 mg plus placebo, or tadalafil 40 mg plus placebo. In this pre-specified subgroup analysis, we compared the efficacy data between those with functional class (FC) II vs. FC III symptoms at baseline. Results: This analysis included 500 participants in the previously defined primary analysis set (n = 155 FC II, n = 345 FC III). Comparing combination therapy to pooled monotherapy, the risk of clinical failure events was reduced by 79% (hazard ratio, 0.21 [95% confidence interval: 0.071, 0.63]) for FC II patients and 42% (hazard ratio, 0.58 [95% confidence interval: 0.39, 0.86]) for FC III patients. In a post-hoc analysis, the risk of first hospitalization for worsening PAH was also reduced by combination therapy, particularly for FC II patients (0 combination vs. 11 [14%] pooled monotherapy). Adverse events were frequent but comparable between the subgroups. Conclusions: Treatment benefit from initial combination therapy appeared at least as great for FC II as for FC III participants. Hospitalizations for worsening PAH were not observed in FC II participants assigned to combination. The present data support an initial combination strategy for newly diagnosed patients even when symptoms are less severe.